Quality Standards of Preclinical Pharmacological Studies - G. N. Engalycheva; R. D. Syubaev; D. V. Goryachev (Регуляторные исследования и экспертиза лекарственных средств, 2019)
The quality and effectiveness of preclinical trials of medicines depend on compliance with the Good Laboratory Practice (GLP) principles. At the same time, the data of the World Health Organisation (WHO) and the analysis of the regulatory framework suggest that the reliability and reproducibility of the results of basic biomedical research are currently a very urgent problem in medicine development. Due to the exploratory nature of studies related to confirmation of scientific hypotheses, and the variety of methodological approaches used, strict GLP criteria cannot be applied to all types of pharmacological studies. According to international acts, GLP principles have the status of requirements and regulate the quality of preclinical safety studies as represented by well-standardised «batteries of tests» used in toxicological studies and safety pharmacology studies, but they do not apply to studies of primary pharmacodynamics which determine potential therapeutic efficacy of the medicinal product. Foreign regulators recommend applying GLP principles to secondary pharmacodynamics studies as well, especially if this type of research makes an important contribution to the safety assessment of medicines. Thus, studies of pharmacological activity of medicines, which are crucial in assessing the prospects of the candidate medicine at the preclinical stage, are mostly «unregulated studies», the results of which may be incorrect. The article discusses the system of regulation of pharmacological studies, including principles of planning and implementation of these studies, as set out in recommendations on Quality Practice in Basic Biomedical Research (QPBR). The application of QPBR principles ensures reliability and reproducibility of the results of preclinical pharmacological studies and increases their scientific and practical value in the development of new medicines.